Patient preferences regarding intraoperative versus external beam radiotherapy for early breast cancer and the impact of socio-demographic factors - Spaich, Saskia; Krickeberg, Sophie; Hetjens, Svetlana; Wenz, Frederik; Sütterlin, Marc (Archives of gynecology and obstetrics, 2019)
PurposePatient comfort and preference have steadily gained attention in radio-oncologic treatment of breast cancer. Therefore, the purpose of this investigation was to further explore patient preferences in choosing between intraoperative radiotherapy (IORT) and external beam radiotherapy (EBRT).MethodsWe prospectively analysed data of 101 women, who were candidates for breast-conserving surgery with adjuvant radiotherapy. A two-part video was shown to patients: an educational section about EBRT/IORT, followed by a preference elicitation section focusing on additional accepted risk (AAR) of recurrence after either treatment. Furthermore, participants completed a questionnaire to identify factors that influence patient preference of radiation modality.ResultsThe data demonstrate that 42.5% of patients would accept additional risk of recurrence for IORT versus 9% AAR for EBRT, while 48.5% of patients would not accept any additional risk, yet would choose IORT over EBRT if risks of recurrence were equivalent. When combining patient preferences and the results from the questionnaire, no single socio-economic/-demographic factor was found to significantly correlate with AAR of IORT.ConclusionOur study confirms the existence of subgroups of breast cancer patients who would accept an additional risk of recurrence associated with choice of radiation modality to receive a single dose of IORT as adjuvant radiotherapy for breast cancer instead of EBRT over several weeks; yet our data fail to identify a single factor significantly associated with these patient preferences and, therefore, helpful for individualised decision-making processes.
Published online: 4 January 2019
Gesehen am 16.05.2019